Associations between Overall and Abdominal Obesity and Suicidal Ideation among US Adult Women - Guixiang Zhao; Chaoyang Li; Earl S. Ford; James Tsai; Satvinder S. Dhingra; Janet B. Croft; Lela R. McKnight-Eily; Lina S. Balluz (Journal of Obesity)
Obesity is associated with increased risks for mental disorders. This study examined associations of obesity indicators including body mass index (BMI), waist circumference, and waist-height ratio with suicidal ideation among U.S. women. We analyzed data from 3,732 nonpregnant women aged ≥20 years who participated in the 2005–2008 National Health and Nutrition Examination Survey. We used anthropometric measures of weight, height, and waist circumference to calculate BMI and waist-height ratio. Suicidal ideation was assessed using the Item 9 of the Patient Health Questionnaire-9. Odds ratios with 95% conference intervals were estimated using logistic regression analyses after controlling for potential confounders. The age-adjusted prevalence of suicidal ideation was 3.0%; the prevalence increased linearly across quartiles of BMI, waist circumference, and waist-height ratio (P for linear trend <0.01 for all). The positive associations of waist circumference and waist-height ratio with suicidal ideation remained significant (𝑃<0.05) after adjustment for sociodemographics, lifestyle-related behavioral factors, and having either chronic conditions or current depression. However, these associations were attenuated after both chronic conditions and depression were entered into the models. Thus, the previously reported association between obesity and suicidal ideation appears to be confounded by coexistence of chronic conditions and current depression among women of the United States.